2018
DOI: 10.1038/s42003-018-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectral signature reflects transcriptomic features of antibiotic resistance in Escherichia coli

Abstract: To be able to predict antibiotic resistance in bacteria from fast label-free microscopic observations would benefit a broad range of applications in the biological and biomedical fields. Here, we demonstrate the utility of label-free Raman spectroscopy in monitoring the type of resistance and the mode of action of acquired resistance in a bacterial population of Escherichia coli, in the absence of antibiotics. Our findings are reproducible. Moreover, we identified spectral regions that best predicted the modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 30 publications
2
91
0
Order By: Relevance
“…While some studies demonstrated that the fingerprint region of Raman spectra (200-1800 cm −1 ) were able to analyse the bacterial phenotype under antibiotic influences, and determine the MIC and resistant mechanisms of E. coli in different antibiotics (Athamneh et al, 2014;Teng et al, 2016;Tao et al, 2017;Xu et al, 2017;Germond et al, 2018;Kirchhoff et al, 2018;Novelli-Rousseau et al, 2018), the C-D band from SCRS is a simple and distinguishable Raman biomarker to identify the MA-ARB in environmental samples (Xu et al, 2017). In this study, we demonstrated that the C-D band can be used to identify the MA-ARB in human gut microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies demonstrated that the fingerprint region of Raman spectra (200-1800 cm −1 ) were able to analyse the bacterial phenotype under antibiotic influences, and determine the MIC and resistant mechanisms of E. coli in different antibiotics (Athamneh et al, 2014;Teng et al, 2016;Tao et al, 2017;Xu et al, 2017;Germond et al, 2018;Kirchhoff et al, 2018;Novelli-Rousseau et al, 2018), the C-D band from SCRS is a simple and distinguishable Raman biomarker to identify the MA-ARB in environmental samples (Xu et al, 2017). In this study, we demonstrated that the C-D band can be used to identify the MA-ARB in human gut microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…For intra-dataset analysis, 50% of the spectra were randomly selected as training data, and the remaining 50% were used as test data; the random selection was repeated 100 times. Classification models were built using PCA and quadratic discriminant analysis (QDA) 22 . Likelihood ratios of QDA to discriminate KML1 cells from B cells were calculated, and log-likelihood ratio = 0 was used as threshold value of the discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…S1 and S3). Collecting the full spectrum, including small peaks, will be important for discrimination, as noted in a previous study using a different type of cells 22 . Laser power will need to meet these two requirements.…”
Section: Discussionmentioning
confidence: 99%
“…A normalized spectral data should be used as a training dataset, and an unknown dataset (without label) from a replicate experiment should be used as test data, if possible. NOTE: Discriminant analysis performed on some vector of a principal component analysis (PCA-DA 10 ), projection on latent scores followed by discriminant analysis (PLS-DA), and support vector machines (SVM) 11 are models often used in the field, and each presents different statistical considerations. Preprocessing of data should be performed consequently.…”
Section: Preprocessing Of Spectral Data and Multivariate Analysesmentioning
confidence: 99%
“…NOTES: The VIP score of a variable is calculated as a weighted sum of the squared correlations between the PLS-DA components and original variable. Details regarding PLS and VIP scores algorithm can be found in the literature 11,12 .…”
Section: Preprocessing Of Spectral Data and Multivariate Analysesmentioning
confidence: 99%